2019
DOI: 10.1155/2019/5935640
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Peripheral Immune Function in Reproductive Females with Uterine Leiomyoma

Abstract: Inflammation and immunity are thought as risk factors for uterine leiomyoma; however, detailed reports on this topic are scarce. The present study aimed to analyze the characteristics of immune function and clinical significance of circulating CD4/CD8 T, NK, and γδ T cells in reproductive females with uterine leiomyoma. We analyzed the above-mentioned cells in 30 reproductive females with uterine leiomyoma and 68 healthy females using flow cytometry. After that, the correlation between function of immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, no differences in the number of CD45-positive leukocytes and MCT-positive mast cells have been observed ( 355 ). A recent study in a Chinese population demonstrated that the numbers of circulating CD4+CD8+ T cells, regulatory T (Treg, CD4+) cells, and T follicular helper (Tfh) cells was notably increased in patients with uterine fibroids relative to the healthy controls, whereas the numbers of natural killer (NK) and delta gamma (γδ) T cells (CD4− CD8−) was reduced ( 356 ). Furthermore, the levels of immune check-point PD-L1 proteins were increased in uterine fibroids compared to adjacent myometrial tissues ( 357 ).…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…However, no differences in the number of CD45-positive leukocytes and MCT-positive mast cells have been observed ( 355 ). A recent study in a Chinese population demonstrated that the numbers of circulating CD4+CD8+ T cells, regulatory T (Treg, CD4+) cells, and T follicular helper (Tfh) cells was notably increased in patients with uterine fibroids relative to the healthy controls, whereas the numbers of natural killer (NK) and delta gamma (γδ) T cells (CD4− CD8−) was reduced ( 356 ). Furthermore, the levels of immune check-point PD-L1 proteins were increased in uterine fibroids compared to adjacent myometrial tissues ( 357 ).…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…In the present study, we focused on functional phenotype alterations of circulating immune cells (CD4+/CD8+ T cells, NK, and γδ T cells) in EP patients, and aimed to discover immune cell related biomarkers associating with pregnancy ability. We used our previously established methodology ( 13 ) to globally evaluate phenotypes of peripheral immune cells, and compare alterations between healthy populations and EP patients of reproductive age. Then we analyzed the immunological relevance between the immune cell phenotypes and pregnancy outcome, indicating that circulating PD1+Vδ1+γδ T cell and the Vδ1/Vδ2 ratio could be developed into the prediction biomarkers for pregnancy ability in endometrial polyp patients of reproductive-age.…”
Section: Introductionmentioning
confidence: 99%
“…Immune and inflammation play important roles in the pathophysiology of the UFs. The peripheral immune cell presented diverse conditions in the UFs patients, for instance, circulating CD4/CD8 T cells were increased while NK cells were decreased ( 45 ). Several studies highlighted the involvement and importance of the macrophages in the inflammation and consequent fibrosis which are typical features of UFs tissue ( 46 ).…”
Section: Discussionmentioning
confidence: 99%